Delaware materials, Frank G. Speck Papers - Speck, Frank G. (Frank Gouldsmith), 1881-1950; Peters, Nicodemus; Moses, Jesse; Springer, Ethel M. (Ethel Maria), 1880-; Witapanóxwe; Wheeler-Voegelin, Erminie, 1903-1988; Montour, Josiah; Washington, Fred; Washington, Jane; Washington, Joe; Greywacz, Kathryn B.; Lilly, Eli, 1885-1977; et al. (1895)
Materials relating to Speck's study of Delaware history, language, and culture. Speck's correspondence with Delaware collaborators in Oklahoma relating to Delaware history, ethnographic data, linguistics, museum specimens, and reservation affairs, etc., might be of particular interest; there are also several tales related by Witapanóxwe, or War Eagle, other tales and texts (some with interlineal translation) from Josiah Montour and other unknown contributors, and 11 sketches of Delaware art designs. Other correspondence touches on Speck's efforts to collect specimens (and individuals and institutions interested in acquiring them), his efforts to collect paintings and sketches of ceremonies and designs, his fieldwork and expenses, financial support from the University of Pennsylvania and Indiana Historical Society, Shawnee data on Oklahoma Delawares, the Big House Ceremony, efforts to acquire a Delaware Big House to erect in Harrisburg, Delawares-as-women, etc. There are also at least 82 pages (in three folders) of Speck's field notes of ethnographic and linguistic data, and over 50 pages (in two folders) of Speck's miscellaneous notes (including some correspondence) on topics such as Gladys Tantaquidgeon and Delaware designs, botanical specimens, linguistic materials, museum specimens, the Walam Olum, the Six Nation Delaware reservation, the celestial bear theme, native religion, reviews of Speck's publications, etc. Other notes cover Delaware grammar and vocabulary, Delaware clans and social organization, dualism in Delaware religion, the influence of Christianity on Delaware religion, the provenance of Delaware museum specimens obtained from Delawares in Oklahoma and Canada, biographical information on Joseph Montur and Nicodemus Peters, etc. There are also various drafts, essays, lectures and other writings by Speck on topics such as Delaware religion, ceremonies, peyote rites, designs, population, remnant populations in the east, history, place names, a Delaware bibliography and a notebook of reports to the ...